2002
DOI: 10.1267/ahc.35.23
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical and Biochemical Studies of Glutathione-Peroxidase(GSH-PO) in Rat Gastric Parietal Cells.

Abstract: Histamine as an acid secretagogue and H 2 -blocker (roxatidine acetate hydrochloride) and a proton pump inhibitor (Omeprazole) as acid secretion inhibitors, in single and repeated doses, were administered to investigate associated lipid peroxidation in rat gastric parietal cells. Methods used included immunohistocytochemical localization and biochemical enzyme activity of glutathione-peroxidase, an enzyme that effectively reduces lipid peroxides. No changes in lipid peroxidation, in response to the H 2 -blocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The response of these cells to exogenous substances can be modulated by a non-dietary, potentially genotoxic factor, namely H. pylori infection, which is a source of neutrophil-generated free radicals, which increase lipid peroxidation in gastric mucosa, resulting in DNA damage [12]. The aim of our investigation was to assess the influence of four antioxidants, melatonin, quercetin and vitamins C and E, on DNA damage and repair induced by surrogate of nitrosamines (MNNG) in association with H. pylori infection in GMCs.…”
Section: Discussionmentioning
confidence: 99%
“…The response of these cells to exogenous substances can be modulated by a non-dietary, potentially genotoxic factor, namely H. pylori infection, which is a source of neutrophil-generated free radicals, which increase lipid peroxidation in gastric mucosa, resulting in DNA damage [12]. The aim of our investigation was to assess the influence of four antioxidants, melatonin, quercetin and vitamins C and E, on DNA damage and repair induced by surrogate of nitrosamines (MNNG) in association with H. pylori infection in GMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Most H 2 O 2 and LOOH are reduced by glutathione peroxidase (GPX). In mammalian cells, classical GPX (cGPX), plasma GPX (pGPX), intestinal GPX (iGPX) and phospholipid hydroperoxide glutathione peroxidase (PHGPX) have been isolated and functionally characterized [5,20,26,27,33,37,46]. Our study showed that PHGPX could reduce DAG-OOH to DAG-OH, an inactive form of neutrophil stimulation, in the presence of reduced form of glutathione, whereas cGPX and pGPX could not [19].…”
Section: Roles Of Anti-oxidative Enzymes As Preventive Agentsmentioning
confidence: 88%